Ethical Considerations in First Nations Counselling and Research - McCormick, Rod M. (Canadian Journal of Counselling and Psychotherapy, 2009)
This paper discusses ethical considerations in First Nations counselling and research. In addition to examining relevant sections of the ethical guidelines of the Canadian Guidance and Counselling Association (CGCA), the paper illustrates the unique ethical issues and considerations that Canadian counselling practitioners and researchers need to be aware of in working with First Nations people.